1998
DOI: 10.1152/ajpheart.1998.275.1.h204
|View full text |Cite
|
Sign up to set email alerts
|

Genistein elicits biphasic effects on L-type Ca2+current in feline atrial myocytes

Abstract: A perforated patch recording method was used to determine the effects of genistein (Gen), a protein tyrosine kinase (PTK) inhibitor, on basal L-type Ca2+ current ( I Ca,L) in feline atrial myocytes. Gen (50 μM) elicited biphasic changes in I Ca,L: an initial inhibition (−55 ± 4%; phase 1) followed by a secondary stimulation (34 ± 9%; phase 2) of I Ca,L. Withdrawal of Gen elicited a further potentiation of I Ca,L (152 ± 19%; phase 3) above control ( n = 46). In general, phase 1 inhibition and phase 3 potentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…Even though an active and direct participation of TKs in L-type Ca 2ϩ channel function in different tissues was demonstrated (29,38,49,52), less is known about VDCC regulation through tyrosine phosphorylation in GH3 cells. Cataldi et al (5) showed that TK inhibition reduced L-type Ca 2ϩ channel activity evoked by 55 mM K ϩ in GH3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Even though an active and direct participation of TKs in L-type Ca 2ϩ channel function in different tissues was demonstrated (29,38,49,52), less is known about VDCC regulation through tyrosine phosphorylation in GH3 cells. Cataldi et al (5) showed that TK inhibition reduced L-type Ca 2ϩ channel activity evoked by 55 mM K ϩ in GH3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the inhibition of tyrosine phosphatase activity by vanadate derivatives has little or no effect on the basal L-type Ca 2 þ current in cardiac myocytes (Wang & Lipsius, 1998;Ogura et al, 1999;Sims et al, 2000;Belevych et al, 2001). On the other hand, inhibition of tyrosine phosphatase activity by PAO, an arsenicbased compound, has been reported to regulate the basal L-type Ca 2 þ channel activity in vascular smooth muscle cells and neurons (Pafford et al, 1995;Wijetunge et al, 1998).…”
Section: Pao Transiently Stimulates the Basal L-type Ca 2 þ Channel Amentioning
confidence: 99%
“…It has been established that this type of regulation involves the production of cAMP and subsequent phosphorylation by protein kinase A (PKA). Tyrosine kinases have also been reported to modulate the activity of cardiac ion channels (Shuba & McDonald, 1997;Zhou et al, 1997;Wang & Lipsius, 1998;Hool et al, 1998;Maier et al, 1999;Mason et al, 2002;Tiran et al, 2003). We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, IGF-1 failed to produce an effect on the L-type Ca 2ϩ current in ventricular myocytes (Sims et al, 2000). On the other hand, the ability of genistein to inhibit the basal L-type Ca 2ϩ current in a variety of cardiac myocytes has been used as an argument to support the idea that these channels may be actually regulated by basal tyrosine kinase activity (Yokoshiki et al, 1996;Hool et al, 1998;Katsube et al, 1998;Wang and Lipsius, 1998;Ogura et al, 1999). Although genistein inhibits PTK activity with little or no effect on serine/threonine protein kinases, it can also produce effects that are unrelated to its ability to inhibit This work was supported by grants from the National Institutes of Health (AG16658 and HL68170).…”
mentioning
confidence: 99%